What is painting? - Bell, Julian, 1952- (London: Thames&Hudson, 2017)
"Yes, but is it art? This lucid book by Julian Bell, himself a painter, confronts the uncertainty many people feel about art today and challenges generally accepted ideas.Now in a completely revised second edition, What is Painting? is a fresh, focused look at painting. Bell addresses questions such as does anything unite those objects we call paintings? and what factors have changed the nature of painting over the last two centuries? by looking at historical evidence and reasoning from common experience. The current shape of painting pushes the book's arguments in new directions and a substantial new chapter, The Arts and Art, speaks to the interplay between 2D work, 3D work, and the immateriality of digital imagery. The text has been revised paragraph by paragraph considering both force of presentation and historical perspective. The intention is to provide a general reader's introduction to theories of painting that is not only reliably informative but stimulating and amusing to read. The book is an introductory guide to art theory for everyone interested in understanding modern art or in making art themselves."--
Images and marks -- Sight and knowledge -- Form and time -- Expression -- The arts and art -- Representation.
First published 1999.
Includes bibliographical references (pages 206-213) and index.
Keywords: Artet boterore; Arti vizual-piktura; Artiste boterore; Painting -- Philosophy-filozofia; Painting, Modern. -- Arti modern; Painting, Modern; Painting -- Philosophy-filozofia; Piktura-teoria-filozofia-analiza-arti mesjetes-arti klasik-arti modern-arti bashkekohor